Kewenangan "Lebih" PPATK Sebagai Modal Penegak Hukum Money Loundry - Budianto, Agus (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
Amandement to the Law on money laundry was based on weakness of law enforcement effectiveness resulting from the unsinergitas (disharmony) between the law enforcement agencies. Does not given the authority to the conduct investigations and inquiries to INTRAC, do not reduces the central role as the leader of INTRAC agent in the eradication of money laundry. Additional powers to the INTRAC as authority 'more' is the INTRAC can request information on the progress of investigation and the inquiries by criminal investigators of origin and / or money laundering. The more authority is run for the benefit of: Handling money laundering effective; Preparation typology and strategic analysis on money laundering and predicate offenses; preparation of consolidated progress in implementing anti-money laundering regime in the context of accountability, and/or the preparation of a report for a meeting National Coordinating Committee for the Prevention and Suppression of Money Laundering. The realization of the implementation these activities, INTRAC can be assistance and request for discussion or presentation, and a criminal investigation of origin and/or money laundering shall fulfill the information request. Thus, there is a relationship that is normative complementarity between investigators with INTRAC within the framework of the creation of a harmonized enforcement of money laundering.